2010
DOI: 10.1097/sla.0b013e3181d96c32
|View full text |Cite
|
Sign up to set email alerts
|

Total Extraperitoneal Inguinal Hernia Repair Compared With Lichtenstein (the LEVEL-Trial)

Abstract: TEP procedure was associated with more adverse events during surgery but less postoperative pain, faster recovery of daily activities, quicker return to work, and less impairment of sensibility after 1 year. Recurrence rates and chronic pain were comparable. TEP is recommended in experienced hands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
0
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(162 citation statements)
references
References 24 publications
15
136
0
11
Order By: Relevance
“…Finally, the recurrence rate in our study was comparable to the recurrence rates reported in the literature for laparoscopic TEP, which range from 0% to around 9% [11,[21][22][23][24][25][26][27][28]. Comparison with our 1 year follow-up study indicates that the rate of recurrence decreases with time.…”
Section: Discussionsupporting
confidence: 76%
“…Finally, the recurrence rate in our study was comparable to the recurrence rates reported in the literature for laparoscopic TEP, which range from 0% to around 9% [11,[21][22][23][24][25][26][27][28]. Comparison with our 1 year follow-up study indicates that the rate of recurrence decreases with time.…”
Section: Discussionsupporting
confidence: 76%
“…This paper has, therefore, been removed from the updated meta-analysis. Since our last analysis, two new studies, comparing Lichtenstein with TEP with long-term follow-up, have been published [6][7][8]. We repeated the meta-analysis (random model) including the new data.…”
Section: Treatment Of Inguinal Herniamentioning
confidence: 99%
“…In the early 1990s, laparoscopic techniques using a tension-free mesh were developed for groin hernia repair. The recurrence rates after laparoscopic repair are comparable to those after open tension-free mesh repair, and range between 2 and 4% [20,22,24,31].…”
Section: Morbidity and Mortality Of Elective Groin Hernia Repairmentioning
confidence: 51%
“…The short-term morbidity, the recurrence rate and the mortality rate are low. Nevertheless, over the past decade, reports have indicated high incidences of chronic pain after tension-free mesh hernia repair, ranging from 2 to 37% [17,[20][21][22][23][24]]. An inconsistency is observed, since these rates exceed the morbidity rates of 8% after elective groin hernia repair mentioned earlier (see Table 1).…”
Section: Discussionmentioning
confidence: 64%